2022
DOI: 10.3390/w14213446
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Contamination of Surface and Groundwater in an Ethiopian Highlands’ Watershed

Abstract: Agricultural intensification in sub-Saharan African countries has significantly increased pesticide applications. Information on pesticide residues and their transport in groundwater and streams is needed to properly manage and reduce any harm to the ecosystem and environment. This information is lacking in the volcanic soils of Ethiopian highlands. Therefore, this study was conducted to assess pesticide concentrations in ground and surface water and their risk to humans and aquatic life. The 9 km2 rural water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…The study confirmed that there were symptoms of surface water pollution from pesticide application practices of farmers in the study area to the extent that cause vomiting and diarrhea to water users immediately after drinking [47]. A study conducted by [48] in Robit Bata of the Lake Tana Watershed confirmed that there was surface and groundwater pollution by persistent pesticides such as chlorpyrifos and endosulfan. A study conducted in the Central Rift Valley of Ethiopia using GC-MS indicated that there was at least one or more pesticide residues per food item, and the amount of pesticide residues in one-third of the sampled food items were above the maximum residual limits [49].…”
Section: Discussionsupporting
confidence: 59%
“…The study confirmed that there were symptoms of surface water pollution from pesticide application practices of farmers in the study area to the extent that cause vomiting and diarrhea to water users immediately after drinking [47]. A study conducted by [48] in Robit Bata of the Lake Tana Watershed confirmed that there was surface and groundwater pollution by persistent pesticides such as chlorpyrifos and endosulfan. A study conducted in the Central Rift Valley of Ethiopia using GC-MS indicated that there was at least one or more pesticide residues per food item, and the amount of pesticide residues in one-third of the sampled food items were above the maximum residual limits [49].…”
Section: Discussionsupporting
confidence: 59%
“…This is because sufficient precipitation and recharge in the wet season diluted salts in groundwater and decreased salinity [ 97 , 98 ]. Higher concentrations of K + were recorded in the wet than in the dry study period, which may be because of leaching from escalated fertilizers, pesticides, and animal wastes in the wet season [ [99] , [100] , [101] ]. Concentrations of K + were by far or slightly lower than the Na + concentrations of all samples in the two study seasons.…”
Section: Discussionmentioning
confidence: 99%
“…The groundwater pollution was more in the rainy period than in the dry period as identified using the DWQI approach. This might be attributed to the groundwater quality degradation, especially in the springs and shallow wells (which cover most of the groundwater samples) concomitant to the possible intrusion of polluted surface flood, and application of fertilizers [ 100 , 109 ]. DWQI results, generally, revealed good and excellent groundwater qualities, implying suitable for drinking purposes.…”
Section: Discussionmentioning
confidence: 99%
“…This poses a threat to nontarget organisms such as humans, wildlife, and invertebrates and can compromise ecosystem sustainability (Gitahi et al, 2002; Osoro et al, 2016). Organochloride pesticides have also been found to be accumulating in groundwater (Sishu et al, 2022) and vegetables (Marete et al, 2020; Omwenga et al, 2021), therefore posing health risks to humans. Short exposure to high doses of pesticides, for example, dichlorodiphenyltrichloroethane (DDT), chlordane, endosulfan, lindane, and diazinon, causes vomiting, tremors, seizures, and skin rashes, whereas long‐term exposure can cause mental confusion and increased risks of liver and kidney cancers (Jayaraj et al, 2016).…”
Section: Organic Pesticide Distribution In Surface Water In Kenyamentioning
confidence: 99%